Exploring mechanisms of acquired resistance to HER2 (human epidermal growth factor receptor 2)-targeted therapies in breast cancer. (11th August 2014) - Creedon, Helen; Byron, Adam; Main, Joanna; Hayward, Larry; Klinowska, Teresa; Brunton, Valerie G.
Abstract : HER2 (human epidermal growth factor receptor 2)-targeted therapy in breast cancer is one of the earliest and arguably most successful examples of the modern class of targeted drugs. Initially identified in the 1980s, the observation that HER2 acts as an independent predictor of poor prognosis in the 20% of breast cancer cases carrying a gene amplification or protein overexpression cemented its place at the forefront of research in this field. The outlook for patients with HER2-positive breast cancer has been revolutionized by the introduction of HER2-targeted agents, such as trastuzumab and lapatinib, yet resistance is frequently encountered and multiple different resistance mechanisms have been identified. We have explored resistance to a novel pan-HER inhibitor, AZD8931, and we examine mechanisms of resistance common to trastuzumab, lapatinib and AZD8931, and discuss the current problems associated with translating the wealth of pre-clinical data into clinical benefit.